Metal stable isotopes fractionation during adsorption - Zijing Li; Yi Huang; Lan Jiang; Hua Tang; Ganghui Jiao; Hang Gou; Wenxian Gou; Shijun Ni (Ecotoxicology and Environmental Safety, 2024)
Isotope technology is an ideal tool for tracing the sources of certain pollutants or providing insights into environmental processes. In recent years, the advent of multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) has enabled the precise measurement of various metal stable isotopes. Due to the presence of ''fingerprint'' properties in various environmental samples, metal stable isotopes have been applied to distinguish the source of contaminants effectively and further understand the corresponding environmental processes. The environmental fate of metal elements is strongly controlled by adsorption, an essential process for the distribution of elements between the dissolved and particulate phases. The adsorption of metal elements on mineral and organic surfaces significantly affects their biogeochemical cycles in the environment. Therefore, it is crucial to elucidate the fractionation characteristics of stable metal isotopes during the adsorption process. In this review, three typical transitional metal elements were selected, considering Mo as the representative of anionic species and Fe and Zn as the representative of cationic species. For Mo, the heavier Mo isotope is preferentially adsorbed in the solution phase, pH has a more significant influence on isotope fractionation, and temperature and ionic strength are relatively insensitive. Differences in coordination environments between dissolved and adsorbed Mo during adsorption, i.e., attachment mode (inner- or outer-sphere) or molecular symmetry (e.g., coordination number and magnitude of distortion), are likely responsible for isotopic fractionation. For Fe, The study of equilibrium/kinetic Fe isotopic fractionation in aqueous Fe(II)-mineral is not simple. The interaction between aqueous Fe(II) and Fe (hydroxyl) oxides is complex and dynamic. The isotope effect is due to coupled electron and atom exchange between adsorbed Fe(II), aqueous Fe(II), and reactive Fe(III) on the surface of Fe (hydroxyl) oxide. For Zn, the heavier Fe isotope preferentially adsorbs on the solid phase, and pH and ionic strength are essential influencing factors. The difference in coordination environment may be the cause of isotope fractionation.